2019
DOI: 10.3727/152599518x15378845225366
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Information Search Behaviors of Adventure Sport Tourists

Abstract: Sport tourism organizations engage in the practice of developing marketing communication and editorial information with the belief that these types of sport- and tourism-related communications are an important element of the sport tourists' prepurchase decision process. However, understanding the extent of its effectiveness requires an investigation into what communication mediums are preferred and from which source do they generally hold in highest regard. Thus, the purpose of this study was to first validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, this is the least important factor in the first stage of the purchasing process. Thus, while it has been shown that it is an important variable in the use of information sources in retail purchases ( Broilo et al, 2016 ) and in the tourism field ( Fodness & Murray, 1999 ; Hungenberg et al, 2019 ), it is less so in the process of searching for information when shopping in a destination. This could be explained by the lack of familiarity among the family and friends of the tourist of the commercial offer at the destination.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is the least important factor in the first stage of the purchasing process. Thus, while it has been shown that it is an important variable in the use of information sources in retail purchases ( Broilo et al, 2016 ) and in the tourism field ( Fodness & Murray, 1999 ; Hungenberg et al, 2019 ), it is less so in the process of searching for information when shopping in a destination. This could be explained by the lack of familiarity among the family and friends of the tourist of the commercial offer at the destination.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al [40] believe that ability means believing others possess the capability or power to do what needs to be done for themselves. Information seekers rely more on information sources with high-level professional knowledge [70], and the information recommended by people with relevant experience is more persuasive [71]. Thus, the hypothesis is as follows: Hypothesis 2a (H2a).…”
Section: Min-twfb and Interpersonal Trust In The Virtual Communitymentioning
confidence: 99%
“…Wasko et al [10] found that individuals with rich knowledge are more inclined to share information and make generous contributions to others. Other research shows that information seekers rely more on information sources with highly professional knowledge, and the information recommended by people who have relevant experience is more persuasive [70,71]. Furthermore, according to the incentive mechanism formulated by the virtual community, valuable contributions, especially when sharing professional knowledge, can improve the reputation of users among their peers [76].…”
Section: Trust-supporting Components Of Min-twfb In the Virtual Commu...mentioning
confidence: 99%
See 1 more Smart Citation